The Concept and Characteristics of Stock Market Indicators PEG and PERG - Błażej Prusak (Contemporary Economics)
In this article there were presented relatively less known in Poland stock market indicators – PEG and PERG. The Author performed a critical analysis of their structure, showing main advantages and limitations of such indicators. Moreover, on the basis of the literature review the usefulness of PEG and PERG in shares’ selection process was analysed.